ECONOMIC REFORM AND ITS IMPACT ON ACHIEVING SUSTAINABLE SOCIAL DEVELOPMENT IN LIGHT OF THE QUR’ANIC VERSES - DR. MOHAMMED YAHYA SAAD AL-MUNSHET (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The study aims to clarify the impact of economic reform on achieving sustainable social development by identifying the most significant factors that influence its realization in light of the objectives and guidance of the Qur’an. This is done through an analytical study that demonstrates the centrality of the economy in social development. The research adopts the inductive–deductive methodology and relies within that framework on analytical methods. The research concluded with several key findings, among the most important of which are: The necessity of establishing economic plans upon which states can depend, especially plans related to income distribution and securing livelihoods so that societies can live in peace and safety. Qur’anic principles—such as justice, solidarity, prohibition of injustice, and excellence in work—form the foundation of building an economically and socially sustainable society. Main Recommendation Encouraging scientific research to develop sustainable economic reform programs and initiatives based on the Qur’an.